Pinching penny - Glaser, Dan, 1989-; Molony, Steven; Meyer, Timothy J.; Clever Lever Pictures (Firm); Leomark Studios (Firm) ([Studio City, CA] : Clever Lever Pictures, 2011)
A hypochondriac named Alex and his accomplice Murphy catapult through a series of slapdash capers in an attempt to pacify their newfound obsession to own everything. But when their crimes turn from petty robbery to kidnapping, their lives take a dangerous turn as they begin spending themselves deeper and deeper into depravity.
Originally released as a motion picture in 2011.
Steven Molony, Timothy J. Meyer, Ginny Glaser, Lauren J. Wertz.
Cinematographer, Alex Welgraven ; editor, Dan Glaser ; music, Kyle Johnston.
Rating: R; bloody violence, drug content and pervasive language.
In English with optional English subtitles; additional Spanish dubbed version with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed May 13, 2016).
Keywords: Criminals -- Drama; Robbery -- Drama; Kidnapping -- Drama; Consumption (Economics) -- Drama; Crime films; Fiction films; Feature films; Detective and mystery films; Internet videos; Streaming video